2021
DOI: 10.26803/ijlter.20.7.19
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Science Teachers’ Creativity and Practice in Malaysia

Abstract: Creative pedagogy has been explored extensively, and previous research suggests that there is a gap between the level and practice of creativity of science teachers, and that it varies by school location. The aim of this study was to determine the levels of creativity, and creativity practice of primary school science teachers, and differences in the levels of creativity and creativity practice of primary school science teachers based on school location. The Torrance Tests of Creative Thinking (TTCT) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Location and environment play an important role in ensuring effective teaching and learning process. Abdullah et al (2021) found that teachers who were in urban areas had a view of creative teaching practices than those who worked at schools in rural areas. Hence, according to Huang et al (2019), urban teachers were more sensitive to student expectations and were inclined to adapt their behaviour or introduce experiments to cater to student needs.…”
Section: Demographic Factormentioning
confidence: 96%
See 4 more Smart Citations
“…Location and environment play an important role in ensuring effective teaching and learning process. Abdullah et al (2021) found that teachers who were in urban areas had a view of creative teaching practices than those who worked at schools in rural areas. Hence, according to Huang et al (2019), urban teachers were more sensitive to student expectations and were inclined to adapt their behaviour or introduce experiments to cater to student needs.…”
Section: Demographic Factormentioning
confidence: 96%
“…In the meanwhile, each research study focused on Korea. (So & Hu, 2019), Israel (Amzaleg & Masry-Herzallah, 2021), Australia (Harris & de Bruin, 2018), New York (Cayirdag, 2017), Malaysia (Abdullah et al, 2021), Spain (Barajas & Frossard, 2018) and England (Hetherington et al, 2020). Figure 3 are shown countries in which the selected studies were conducted.…”
Section: Background Of the Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations